A Role for Dogs in Advancing Cancer Immunotherapy Research - Dow, Steven (Frontiers in Immunology, 2020)
While rodent cancer models are essential for early proof-of-concept and mechanistic studies for immune therapies, these models have limitations with regards to predicting the ultimate effectiveness of new immunotherapies in humans. As a unique spontaneous, large animal model of cancer, the value of conducting studies in pet dogs with cancer has been increasingly recognized by the research community. This review will therefore summarize key aspects of the dog cancer immunotherapy model and the role that these studies may play in the overall immunotherapy drug research effort. We will focus on cancer types and settings in which the dog model is most likely to impact clinical immuno-oncology research and drug development. Immunological reagent availability is discussed, along with some unique opportunities and challenges associated with the dog immunotherapy model. Overall it is hoped that this review will increase awareness of the dog cancer immunotherapy model and stimulate additional collaborative studies to benefit both man and man's best friend.